Faktor·faktor Latar Belakang Yang Berkaitan Dengan Pencapaian Akademik Murid Darjah Satu - Md. Nor, Sharifah (Penerbit Universiti Sains Malaysia, 1991)
This paper discusses factors relating to the academic achievement of Standard One pupils in a school situated in a small town in West Malaysia. The academic records of 144 Standard Three pupils while they were in Standard One were analysed. The dependent variable was test scores obtained at the end of Standard One. Independent variables were race, family income, mothers' education {years of schooling) and fathers' education. Regression was used to analyse data. Findings showed that race {Indian) was negatively associated with achievement. Mothers' education {6-12 years) and Indian mothers' education contribute positively towards achievement. The findings suggest that more need to be done by all parties to improve the education of poor pupils particularly that of the Indian community.